NOWO WYDANY KANCJONAŁ PRUSKI (1741) RELEASED BY JOHANN HEINRICH HARTUNG’S PUBLISHING HOUSE OF KONIGSBERG AGAINST THE BACKGROUND OF THE EARLIER PUBLICATIONS IN KONIGSBERG (in English) - PALUSZAK-BRONKA, ANNA; WRONKOWSKA-DIMITROWA, MIROSŁAWA (Knygotyra, 2015)
Konigsber was a significant centre of printing and publishing activities during the 16–18th centuries. Printing production was not only set by the needs of the society of Ducal Prussia, but also by the ambitions to reach the readers from the neighbouring Polish and Lithuanian lands. Nowo wydany Kancjonał Pruski, whose main editor was the priest Jerzy Wasiański, appeared in 1741, the last edition appeared in 1926. So this songbook circulated till the 20th century. There are nearly 150 editions of this songbook, most of them consisting of more than 50 000 books. In the years 1782–1918 this songbook had one edition per year on a regular basis. Nowo wydany Kancjonał Pruski, or Kancjonał mazurski, was the most popular songbook among the Mazurians till beginning of the 20th century.